Flight tests on a torquemeter installed on Gipsy Queen 71 engine on dove aircraft - Robertson, I. A. (College of Aeronautics, 1955)
The torquemeter failed at 178 hrs. 50 minutes flying. Torquemeter powers compared with engine powers deduced from maker's curves give the following results: 1) At low BHP readings the torquemeter tends to over-read 2) At high BHP readings the torquemeter tends to under-read.